Knowledge Spillovers, ICT and Productivity Growth1. (24th March 2017) - Corrado, Carol; Haskel, Jonathan; Jona‐Lasinio, Cecilia
Abstract: This paper looks at the channels through which intangible assets affect productivity growth. The econometric analysis exploits a new data set on intangible investment (INTAN‐Invest) in conjunction with EUKLEMS productivity estimates for 10 EU member states from 1998 to 2007. We find that (a) the output elasticity of intangible capital depends upon ICT intensity, consistent with complementarities between ICT and intangible capital; (b) non‐R&D intangible capital has a higher estimated output elasticity than its factor share, as does (c) an index of labour composition. The last two findings are consistent with growth spillovers from investments in knowledge‐based/intangible capital and skills.